The Expression of Proteins Related to Serotonin Pathway in Pulmonary Arteries of Dogs Affected With Pulmonary Hypertension Secondary to Degenerative Mitral Valve Disease - Sakarin, Siriwan; Surachetpong, Sirilak Disatian; Rungsipipat, Anudep (Frontiers in Veterinary Science, 2020)
Abstract Background: Pulmonary hypertension (PH) can cause medial thickening, a hallmark of pulmonary arterial remodeling. The serotonin (5HT) pathway has been suggested as a factor associated with PH by inducing pulmonary arterial smooth muscle cells (SMCs) proliferation, a major cause of medial thickening. This study aims to demonstrate the expression of molecules in the 5HT pathway in the pulmonary artery of dogs affected with PH secondary to degenerative mitral valve disease (DMVD) compared to DMVD and healthy control dogs. Materials and Methods: The study included lung samples from the carcasses of 19 older small-breed dogs (Control n=5, DMVD n=7, DMVD+PH n=7). Lung tissue sections were performed Hematoxylin and Eosin staining for measuring the percentage of medial thickness and immunohistochemistry for evaluating the expression of proteins in the 5HT pathway including serotonin transporter (SERT), serotonin 2A receptor (5HT2A), tryptophan hydroxylase 1 (TPH1), extracellular regulated kinase 1/2 (ERK1/2) and phosphorylated ERK1/2 (pERK1/2). Results: Medial thickening of the pulmonary arteries was found in the DMVD and DMVD+PH groups compared to the control. The medial thickening of the DMVD+PH group was increased significantly compared to that in the DMVD group. Intracytoplasmic expression of proteins related to the 5HT pathway was mainly presented in the medial layer of the pulmonary arteries. The control group showed a low expression of proteins related to the 5HT pathway. An intensive expression of SERT, 5HT2A, TPH1 and ERK1/2 protein was seen in the DMVD and DMVD+PH groups. Interestingly, pERK1/2 was strongly represented only in the DMVD+PH group. Conclusions: Overexpression of proteins related to the 5HT pathway including SERT, 5HT2A, TPH1, ERK1/2 and pERK1/2 was associated with medial remodeling in dogs affected with secondary to DMVD.